Advanced design of wastewater treatment plants emerging research and opportunities - Hussain, Athar 1976-; Bhattacharya, Ayushman 1998- (A volume in the Advances in environmental engineering and green technologies (AEEGT) book series, 2019)
"This book examines the various treatment technologies and their application for producing reuse quality water from wastewater. It also covers topics such as the basic philosophy of wastewater treatment, designing principles of various wastewater treatment units, conventional treatment systems, and advanced treatment processes"--